The concept and legal significance of the place of arbitration in Kazakhstan - Ossipov Y.B., Suleimenov M, Ilyassova K.M., Kaziyeva G.T., Duysenova A., (Opción, 2019)
The article considers questions about the concept and legal significance of the place of arbitration under the legislation of the Republic of Kazakhstan via comparative qualitative research methods. As a result, the law in force at the place of arbitration (lex arbitri) defines the requirements for arbitration of disputes. In conclusion, the Kazakhstani legislative concept of the place of arbitration does not allow to consider such a concept as conditional or fictitious, since the place of holding the meetings of the arbitration and making a decision is attached to the place of arbitration.